Maternal and perinatal outcomes in pregnancy associated with placenta previa - Gupta, Jyoti; Hak, Jyoti; ., Anuradha; ., Harleen; Mehta, Lakshay (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Placenta previa is associated with increased maternal and perinatal complications like malpresentation, premature labor, higher rates of caesarean section, peripartum hysterectomies, postpartum hemorrhage, sepsis, shock and retained placenta and even death. Antepartum haemorrhage may frequently result in low birth weight babies, preterm labour or repeated small events of haemorrhage causing chronic placental insufficiency and foetal growth retardation or intrauterine fetal death. Methods: This was a prospective study conducted in the department of obstetrics and gynaecology, SMGS, hospital, Jammu over a period of 1 year. All admitted cases of placenta previa were included in the study. Results: The total numbers of deliveries in one our hospital were 18567 during the study period. 364 patients admitted with antepartum heamorrhage so the incidence of APH in our hospital was 1.96%. 157 cases out of 346 were of placenta previa. It was observed that placenta previa cases were highest in the maternal age group of 26-30 yrs, i.e. 55.42%, 71.97% were multigravidae and 26.75% with prior caesarean section. 15.92% had undergone peripartum hysterectomy due to massive PPH. The percentage of perinatal death was 18.23% and the main cause was prematurity. Conclusions: Based upon observation made during this study, it is concluded that placenta previa is a serious condition with significant maternal and perinatal morbidity and mortality. Improvements in management of placenta previa have helped in improving neonatal survival and reduce maternal morbidity and mortality.